Gestalt approach group counseling implementation in junior high school: systematic literature review - Wudy, Simon; Suranata, Kadek; Dharmayanti, Putu Ari (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
Group Counseling is an excellent support service to help with personal skills development, prevention, and dealing with interpersonal conflicts or problem solving. Gestalt counseling believes that through awareness, there must be change. The focus is on helping individuals through their transition from a state that is always assisted by the environment to a state that is independent. The main concept of the gestalt approach is the here and now and unfinished business. This study aims to collect and analyze relevant articles to find out the progress of the articles, the methods or techniques used, and to find out whether the Gestalt approach to counseling can be implemented in junior high schools.The method in this study uses a Systematic Literature Review, namely research to identify, evaluate, and interpret all relevant research results related to certain research questions, certain topics, or phenomena of concern, searching for journal article data sources is done through the Publish or Perish application, documentation of scientific journal articles that have been published from the Google scholar, Croosref and GARUDA databases in the last 5 years and in working on these journals/papers using the Mendeley application and VOSviewer, one of the software that can be used to build and visualize bibliometric networks using the keywords